Out in Africa : LGBT Organizing in Namibia and South Africa - Currier, Ashley (Book collections on Project MUSE., 2012)
Visibility matters to activists - to their social and political relevance, their credibility, their influence. But invisibility matters, too, in times of political hostility or internal crisis. This book examines how Namibian and South African lesbian, gay, bisexual, and transgender (LGBT) organisations have cultivated visibility and invisibility as strategies over time. As such, it reveals the complexities of the LGBT movements in both countries as these organisations use Western terminology and notions of identity to gain funding even as they work to counter a perception that they are 'un-African'.